Fluorescent Nanodiamond: A Versatile Tool for Long-Term Cell Tracking, Super-Resolution Imaging, and Nanoscale Temperature Sensing - Hsiao, Wesley Wei-Wen; Hui, Yuen Yung; Tsai, Pei-Chang; Chang, Huan-Cheng (Accounts of chemical research, 2016)
Fluorescent nanodiamond (FND) has recently played a central role in fueling new discoveries in interdisciplinary fields spanning biology, chemistry, physics, and materials sciences. The nanoparticle is unique in that it contains a high density ensemble of negatively charged nitrogen–vacancy (NV–) centers as built-in fluorophores. The center possesses a number of outstanding optical and magnetic properties. First, NV– has an absorption maximum at ∼550 nm, and when exposed to green-orange light, it emits bright fluorescence at ∼700 nm with a lifetime of longer than 10 ns. These spectroscopic properties are little affected by surface modification but are distinctly different from those of cell autofluorescence and thus enable background-free imaging of FNDs in tissue sections. Such characteristics together with its excellent biocompatibility render FND ideal for long-term cell tracking applications, particularly in stem cell research. Next, as an artificial atom in the solid state, the NV– center is perfectly photostable, without photobleaching and blinking. Therefore, the NV-containing FND is suitable as a contrast agent for super-resolution imaging by stimulated emission depletion (STED). An improvement of the spatial resolution by 20-fold is readily achievable by using a high-power STED laser to deplete the NV– fluorescence. Such improvement is crucial in revealing the detailed structures of biological complexes and assemblies, including cellular organelles and subcellular compartments. Further enhancement of the resolution for live cell imaging is possible by manipulating the charge states of the NV centers. As the “brightest” member of the nanocarbon family, FND holds great promise and potential for bioimaging with unprecedented resolution and precision. Lastly, the NV– center in diamond is an atom-like quantum system with a total electron spin of 1. The ground states of the spins show a crystal field splitting of 2.87 GHz, separating the m s = 0 and ±1 sublevels. Interestingly, the transitions between the spin sublevels can be optically detected and manipulated by microwave radiation, a technique known as optically detected magnetic resonance (ODMR). In addition, the electron spins have an exceptionally long coherence time, making FND useful for ultrasensitive detection of temperature at the nanoscale. Pump–probe-type nanothermometry with a temporal resolution of better than 10 μs has been achieved with a three-point sampling method. Gold/diamond nanohybrids have also been developed for highly localized hyperthermia applications. This Account provides a summary of the recent advances in FND-enabled technologies with a special focus on long-term cell tracking, super-resolution imaging, and nanoscale temperature sensing. These emerging and multifaceted technologies are in synchronicity with modern imaging modalities.